Comment on Awais Ur Rehman, et al. (J Pak Med Assoc. 72: 2180-2183, 2022) Assessment of quality of life of stroke survivors and their caregivers presenting to a tertiary care hospital in Pakistan - Khalil, Muhammad Tawab; Rathore, Farooq Azam (Journal of the Pakistan Medical Association, 2023)
Madam, We have read the article titled “Assessment of quality of life (QOL) of stroke survivors and their caregivers presenting to a tertiary care hospital in Pakistan” by Rehman et al with great interest.1. They have highlighted the issue of reduced QOL in all domains in stroke survivors. This is an important finding and addition to the stroke literature from Pakistan. Unlike many other diseases, stroke is a disease which affects the whole family. The disability resulting from a stroke can be significant, persisting for months to years and often requires constant attendant care. In many cases caregivers cater for every need of the stroke survivor including mobility, toilet care, exercise and feeding. This creates a constant stressful situation for the caregivers resulting in a poor QOL As Rehabilitation Medicine physicians who regularly attend post stroke patient and advice rehabilitation plan, we have some observations and comments on the manuscript which need clarification..